Mechanism of improvement in atrial functional mitral regurgitation after catheter ablation for atrial fibrillation: Three‐dimensional analysis using multislice computed tomography. Issue 2 (4th November 2021) - Tsujisaka, Yuta; Kaji, Shuichiro; Kim, Kitae; Pak, Misun; Sasaki, Yasuhiro; Kitai, Takeshi; Kobori, Atsushi; Furukawa, Yutaka
Abstract: Background: Several factors associated with atrial functional mitral regurgitation development have been reported; however, geometric changes in the mitral apparatus after catheter ablation for atrial fibrillation have not been sufficiently investigated. This study aimed to clarify what determines improvements in atrial functional mitral regurgitation after sinus rhythm restoration in patients who underwent catheter ablation for atrial fibrillation by using multislice computed tomography. Methods: We analysed volumetric multislice computed tomography images of 44 atrial fibrillation patients with significant atrial functional mitral regurgitation (moderate or worse) before and after catheter ablation. We measured the three‐dimensional geometry of the mitral apparatus including the mitral annular area and interpapillary muscle distance. We calculated the differences before and after catheter ablation (Δmitral annular area, Δinterpapillary muscle distance) and assessed mitral regurgitation severity based on the mitral regurgitant jet area and its changes before and after catheter ablation (Δjet area) using transthoracic echocardiography. Results: After catheter ablation, the jet area was significantly decreased. The left ventricular ejection fraction was significantly increased and the left ventricular volume had a decreasing trend. The Δjet area was significantly correlated with the Δinterpapillary muscle distance ( r  = .43; p  = .004). The Δinterpapillary muscle distance was the strongest determinant of improvements in atrial functional mitral regurgitation severity ( p  = .026). Conclusions: Decreased interpapillary muscle distance was strongly associated with improvements in atrial functional mitral regurgitation. Amelioration of left ventricular dysfunction by sinus rhythm restoration might be related to improvements in atrial functional mitral regurgitation after catheter ablation.